Perencanaan Kota Berbasis Kontradiksi: Relevansi Pemikiran Henri Lefebvre dalam Produksi Ruang Perkotaan Saat Ini - Sudaryono, Sudaryono (Center for Research and Community Services ITB, 2008)
As one of the most influential philosophers of the 19′th century, Henri Lebfebre shows his significant contribution to the recent thinking of urban space. His thinking was built on the basis of his critiques to the development of urban space which according to his view was dominated by he called as “single force”, “single center”, “monocentric strategy”, alias “world market strategy”. Under such mainstream of urban force, the urban spaces then have been produced as “space of consumption” which further leads to the “consumption of space”. This phenomenon was viewd by him as dangerous situation where the city will destroy itself in the future. This paper aims to discuss his main ideas and thinking in terms of (i) spatial justice and the right to the city, (ii) multi dimensional of urbanism, (iii) urban everyday life and space demand, (iv) dialectic of abstract and concrete spaces, (v) metropolization, (vi) space and centrality, (vii) space and global capital, (viii) space of flow, (ix) right to difference of space, and (x) politics and space. Lefebre ends up his critiques with three main proposals: (i) mobilization of difference in a single movement, (ii) bringing-together of dissociated elements, and (iii) unifications of disparate tendencies. The thinking of Lefebvre contributes much to the development of recent concept of urban space. It teaches us that the core problem of urban spaces is laid on its own contradictory space; without knowing this core problem any problem, any solutions to the urban spatial problems will remain in big questions. Lefebvre believes that urban planning is still relevant to be taken as a way of solution to the contradictory spaces. Urban planning should develop a new method of work. it should work on the basis of empirical problems by knowing contradictory situations of urban space, and not to start with normative and theoretical propositions. Urban planning should bring a city to a situaton what he called as “appropriation” and not “domination”